Internalisasi Nilai-Nilai Budi Luhur dalam Pembinaan Seni Beladiri Persaudaraan Setia Hati Terate (PSHT) di Kab. Lombok Timur - Wulan, Mala Aulia; Wahid, Lalu Abdurrahman; Muhtasar, Muhtasar (Lembaga Yasin AlSys, 2025)
This study is motivated by the declining moral values among the younger generation, influenced by technology and globalization, as reflected in weakened attitudes of politeness, honesty, responsibility, and tolerance. In this context, Persaudaraan Setia Hati Terate (PSHT), as a traditional martial arts organization, plays a strategic role in instilling noble values and fostering youth character development. The research aims to identify the moral values taught and analyze the internalization process within PSHT’s martial arts training in East Lombok Regency. A descriptive qualitative approach was employed, using participant observation, semi-structured interviews, and documentation. Research subjects were selected purposively and included branch and sub-branch leaders, trainers, and PSHT members from the Sikur, Terara, and Montong Gading areas. Data were analyzed through reduction, presentation, interpretation, and conclusion drawing and verification. The findings reveal that the internalized values include honesty, responsibility, politeness, empathy, tolerance, maturity, and wisdom. The internalization process is carried out systematically through physical training integrated with mental and spiritual development, shaping members who are resilient both physically and morally. The study concludes that PSHT has successfully instilled noble values through structured and consistent character education. The implication is that PSHT can serve as a model for youth character development, offering a viable solution to the moral crisis of the modern era.